1990
DOI: 10.1128/mcb.10.3.1134
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional RNA helicase activity of eucaryotic translation initiation factors 4A and 4F.

Abstract: The mechanism of ribosome binding to eucaryotic mRNAs is not well understood, but it requires the participation of eucaryotic initiation factors eIF-4A, eIF-4B, and eIF-4F and the hydrolysis of ATP. Evidence has accumulated in support of a model in which these initiation factors function to unwind the 5'-proximal secondary structure in mRNA to facilitate ribosome binding. To obtain direct evidence for initiation factor-mediated RNA unwinding, we developed a simple assay to determine RNA helicase activity, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
424
4
2

Year Published

1995
1995
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 581 publications
(455 citation statements)
references
References 68 publications
25
424
4
2
Order By: Relevance
“…However, an appreciable fraction of eIF4A is not bound in eIF4F 77 . eIF4A also associates with the initiation factors eIF4B and eIF4H, which are closely related RNA-binding proteins that enhance eIF4A association with RNA 84 and thereby increase the ability of eIF4A to unwind RNA and hydrolyse ATP in an RNA-stimulated fashion 85,86,87 . Together, these factors all promote formation of a translation initiation complex that allows binding of the small 40S ribosomal unit and other initiation factors to mRNA 88 .…”
Section: Nuclear Specklesmentioning
confidence: 99%
“…However, an appreciable fraction of eIF4A is not bound in eIF4F 77 . eIF4A also associates with the initiation factors eIF4B and eIF4H, which are closely related RNA-binding proteins that enhance eIF4A association with RNA 84 and thereby increase the ability of eIF4A to unwind RNA and hydrolyse ATP in an RNA-stimulated fashion 85,86,87 . Together, these factors all promote formation of a translation initiation complex that allows binding of the small 40S ribosomal unit and other initiation factors to mRNA 88 .…”
Section: Nuclear Specklesmentioning
confidence: 99%
“…Intriguingly, the DEAD box helicases comprise a family of proteins that catalyze unwinding of RNA. Members of this family include proteins involved in both translation initiation (eIF4A) and ribosomal RNA processing (Pause et al, 1994;Rozen et al, 1990). Although the biochemical function of this Myc target is currently unknown, its homologue in Drosophila has been named pitchoune as a consequence of the small size phenotype which results from its loss (Za ran et al, 1998).…”
Section: C-myc Target Genes and Growth Controlmentioning
confidence: 99%
“…polypeptide has been difficult because translation factors mostly function as heteromericcomplexes. It has been shown that eIF-4A is an RNA helicase (Rozen et al, 1990;Pause & Sonenberg, 1992), eIF-4B, which contains the conserved eukaryotic RNAbinding domain, is an mRNA-binding protein (Naranda et al, 1994), and EF-la and EF-2 are GTPases (Lauer et al, 1984). eIF-5 also has been shown to possess GTPase activity (Trachsel & Staehelin, 1978;Brown-Luedi et al, 1982), even though the sequence of this protein does not contain the classical GTPbinding motifs Chakravarti & Maitra, 1993; E.V.…”
mentioning
confidence: 99%